Potential antifilarial activity of the leaves and seeds extracts of Psoralea corylifolia on cattle filarial parasite Setaria cervi - Ahmed, Qamar Uddin; Parveen, Nazneen; Khan, N. U.; Singhal, K. C. (Elsevier Ireland Ltd, 2002)
The effect of aqueous and alcohol extracts of the leaves and seeds of Psoralea corylifolia , on the spontaneous movements of both the whole worm and the nerve muscle preparation of Setaria cervi and on the survival of microfilariae in vitro was studied. Alcohol extracts of both leaves and seeds caused the inhibition of spontaneous movements of the whole worm and the nerve muscle preparation of S. cervi , characterised by initial, short lasting small increase in tone of contractions followed by paralysis. The initial stimulatory effect was not observed by alcohol extract of leaves on nerve muscle preparation. The concentrations required to inhibit the movements of whole worm and nerve muscle preparations for alcohol extracts of leaves and seeds were 160, 30, and 150, 20 mg/ml, respectively suggesting a cuticular permeability barrier. Alcohol extracts of both leaves and seeds caused death of microfilariae in vitro, LC50 and LC90 being 15 and 25 ng/ml for alcohol extract of leaves and 12 and 18 ng/ml for alcohol extract of seeds,respectively.